Kritik Stereotipe Perempuan Pekerja Domestik di Media Sosial : Analisis Wacana Kritis Postingan Akun Instagram @kalis.mardiasih - Lukman Hakim (Airlangga University, 2023)
Domestic work is a household-related activity and is mostly done by women. There are many negative stereotypes about women as domestic workers. One of the young activists, Kalis Mardiasih is quite critical in responding to gender issues on his Instagram account. The study aims to analyze the discourse behind posts @kalis.mardiasih related to stereotypes of women as domestic workers. This study uses the critical discourse analysis method of Norman Fairclough. The result of this study show that Kalis Mardiasih means women are more often victims according to the passive stigma attached to him. From the mental side, the female consciousness of accepting the stereotypes makes women only classified as a second-class human being that can be objectified. In addition, Kalis also responded through posts on her Instagram account about the stereotypes of female domestic workers by putting pressure on the meaning of the images and symbols posted, such as the role of women in the household. In his post, Kalis Mardiasih gave an emphasis on pictures f women crying while hanging children accompanied by symbols holding household appliances. In addition, Kalis Mardiasih also made writing with a thick style so that the essence of gender equality can be accepted by citizens.